The ECO-ICBT database of cross-border trade in agricultural products in ECOWAS - Bouët, Antoine; Cissé, Brahima; Kam, Dieudonné; Kanoute, Elhadji Samba; Konombo, Oumar Abdou Nassur; Matitoma, Justin Motchosso; Sack, Seydou; Sy, Abdourahmane; Todina, Ngaye; Traoré, Fousseini (Association Ouest Africaine du Commerce Transfrontalier des produits Alimentaires, Agro-sylvo-pastoraux et Halieutiques, 2021)
Recent reports and economic literature clearly show that intra-African trade is not well measured by official databases, such as those compiled by NSOs and international institutions. This is especially true in West Africa since ECOWAS eliminated duties on intraregional trade. ECOWAS is a customs union with free trade among member countries for produits du cru (local products). The lack of high-quality trade data is largely explained by the weakness of formal data collection systems (hampered by underdeclaration, misclassification, lack of incentives for customs agents due to exoneration of customs duties, and so on). Yet accurate trade statistics are paramount for designing policies for food security, monitoring progress toward important goals (such as the Malabo target or the African Continental Free Trade Area) and providing the private sector with valuable information.